2020
DOI: 10.1186/s13148-020-00918-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide DNA methylation profiling of preeclamptic placenta according to severe features

Abstract: Background: Preeclampsia (PE) is an obstetric disorder with significant morbidities for both the mother and fetus possibly caused by a failure of the placental trophoblast invasion. However, its pathophysiology largely remains unclear. Here, we performed DNA methylation profiling to determine whether differential patterns of DNA methylation correlate with PE and severe features of PE. Materials and methods: We extracted DNA from placental tissues of 13 normal, five PE, and eight PE pregnant women with severe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Lastly, we evaluated whether the 45 CpGs overlapped lists of CpGs with PE-associated placental DNAme found in eleven previous studies (Martin et al, 2015;Yeung et al, 2016;Berg et al, 2017;Kim et al, 2017;Zhao et al, 2017;Wilson et al, 2018;Wang et al, 2019a;Lim et al, 2020;van den Berg et al, 2020;Workalemahu Tsegaselassie et al, 2020). Of the 45 eoPred CpGs, 36 overlapped hits found to be EOPE-associated by Wilson et al, 2018, which is to be expected given that the discovery dataset (GSE100197) was included in our training group.…”
Section: Subset Of Validationmentioning
confidence: 93%
See 1 more Smart Citation
“…Lastly, we evaluated whether the 45 CpGs overlapped lists of CpGs with PE-associated placental DNAme found in eleven previous studies (Martin et al, 2015;Yeung et al, 2016;Berg et al, 2017;Kim et al, 2017;Zhao et al, 2017;Wilson et al, 2018;Wang et al, 2019a;Lim et al, 2020;van den Berg et al, 2020;Workalemahu Tsegaselassie et al, 2020). Of the 45 eoPred CpGs, 36 overlapped hits found to be EOPE-associated by Wilson et al, 2018, which is to be expected given that the discovery dataset (GSE100197) was included in our training group.…”
Section: Subset Of Validationmentioning
confidence: 93%
“…In the human placenta, DNA methylation (DNAme) has a unique profile that shifts throughout gestation in association with changes in cell composition, gene expression, and in response to pregnancy complications, among other factors (Robinson and Price, 2015;Yuan et al, 2021). Many studies have reported PE-associated alterations in placental DNAme (Blair et al, 2013;Chu et al, 2014;Martin et al, 2015;Yeung et al, 2016;Kim, 2017;Wilson et al, 2018;Wang et al, 2019a;Lim et al, 2020;Workalemahu Tsegaselassie et al, 2020), but findings are not consistently reproduced across studies (Cirkovic et al, 2020). Discrepancies between studies in definitions of PE used, study design (e.g., analysing all PE compared to analysing specific subtypes such as EOPE, LOPE), the use of different metrics to assess reproducibility (e.g., a CpG found to be significantly differentially methylated in one cohort may not replicate in an independent cohort, but a proximal and correlated CpG might), and platforms used to measure DNAme, among others, can contribute to poor reproducibility across studies.…”
Section: Introductionmentioning
confidence: 99%
“…IUGR affects up to 12% of all pregnancies and is characterized by low fetal growth (<10th percentile) and increased risk of fetal and neonatal morbidity and mortality [ 5 , 6 ]. Additionally, several studies have reported long-term sequela of IUGR complications including adult hypertension, heart disease, stroke, and diabetes [ 7 , 8 , 9 , 10 , 11 ]. While IUGR and PE are different obstetric complications, they exhibit similar pathologies including placental apoptosis, increased placental inflammation, and abnormal vascularization of maternal placenta tissues [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations to the epigenetic profile of placental tissues have been reported in cases of PE and IUGR [ 10 , 11 , 12 ]. The presence of epigenetic abnormalities in both PE and IUGR proposes a possible correlational relationship between epigenomic alterations and PE/IUGR pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the link between maternal prenatal mental health status and HPA axis function may be mediated by DNA methylation, a possible epigenetic mechanism that eventually leads to adverse outcomes for the mother ( 25 ) and infant ( 26 ). DNA methylation regulates gene expression but does not change the sequence of DNA.…”
Section: Introductionmentioning
confidence: 99%